Using Low-Code Technology to Develop Tasks in an Interactive Testing System - Andrey Kraev; Svetlana Filippova (Современные информационные технологии и IT-образование)
Currently, for the development of certain solutions, they are actively switching to Low-code technologies, i.e. they use blocks with ready-made code and get the final product with the necessary functionality. This speeds up work with typical tasks, eliminates repetitive actions, helps minimize the manual coding process and allows users with varying degrees of technical training to create the required solutions. In the article, the authors describe the use of this technology in the formation of tasks in the «Electronic Score» dialog system, which was developed by the authors based on the use of client-side scripting technology and for a number of years has been used to test students at the Faculty of the Moscow State University, as well as for individual classes. Early versions of the system required advanced programming knowledge from task compilers. Thanks to the modification, the use of the system will be possible for teachers who do not have extensive knowledge in the field of coding and will expand the range of prospective users of the system.